The double‐edged sword of endoplasmic reticulum stress in uremic sarcopenia through myogenesis perturbation. Issue 3 (29th January 2018) - Jheng, Jia‐Rong; Chen, Yuan‐Siao; Ao, Un Iong; Chan, Ding‐Cheng; Huang, Jenq‐Wen; Hung, Kuang‐Yu; Tarng, Der‐Cheng; Chiang, Chih‐Kang
Abstract: Background: Sarcopenia is the age‐related degeneration characterized with the decline of skeletal muscle mass, strength, and function. The imbalance of protein synthesis and degradation which jeopardizes immune, hormone regulation, and muscle‐motor neuron connection is the main cause of sarcopenia. There is limited knowledge regarding molecular mechanism of sarcopenia. As the endoplasmic reticulum is the control centre of the protein syntheses and degradation, we hypothesized that endoplasmic reticulum stress and unfolded protein response (UPR) play an important in the development of sarcopenia. Understanding the sarcopenia molecular mechanisms may benefit the therapeutic diagnosis and treatment in the future. Methods: Mouse myoblast C2C12 cells are exposed to designated time and concentration of indoxyl sulfate (IS), a uremic toxin of chronic kidney disease. The proliferation, differentiation, and the expression of atrogin 1 are examined. The protein and mRNA expression of IS treated‐C2C12 cells are inspected to distinguish the role of ER stress and oxidative stress underlying the sarcopenia. Results: Indoxyl sulfate inhibits myoblast differentiation. We demonstrate that as the number of multi‐nuclei myotube decreased, the differentiation markers including myoD, myoG, and myosin heavy chain are also suppressed. Indoxyl sulfate inhibits myoblast proliferation and induces the myotubular atrophy marker atrogin‐1 protein expression. Indoxyl sulfate stimulates eIF2α phosphorylation and XBP1 mRNA splicing in UPR. Interestingly, the oxidative stress is related to eIF2α phosphorylation but not XBP1 mRNA splicing. The eIF2α phosphorylation triggered by IS reduces myoD, myoG, and myosin heavy chain protein expression, which represents the anti‐myogenic modulation on the early differentiation event. The XBP1 mRNA splicing induced by IS, however, is considered the adaptive response to restore the myogenic differentiation. Conclusions: Our studies indicated that the ER stress and UPR modulation are critical in the chronic kidney disease uremic toxin‐accumulated sarcopenia model. We believe that UPR‐related signals showed great potential in clinical application.